2013
DOI: 10.1021/nn303764k
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon Dynamics in Colloidal Au2Cd Alloy–CdSe Core/Shell Nanocrystals

Abstract: Metal-semiconductor nanocrystal heterostructures are model systems for understanding the interplay between the localized surface plasmon resonances in the metal domain and the relaxation of the excited carriers in the semiconductor domain. Here we report the synthesis of colloidal Au₂Cd (core)/CdSe (shell) nanocrystal heterostructures, which were characterized extensively with several structural and optical techniques, including time-resolved fluorescence and broad-band transient absorption spectroscopy (both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 48 publications
1
30
0
Order By: Relevance
“…The Cd component reacted with the Se, leading to the formation of a Au@CdSe core/shell structure. Pablo et al reported a similar approach to synthesize colloidal Au 2 Cd@CdSe core/shell NPs via AuCd alloy seeds . The internal Cd atoms were partially pulled out to the surface by Se through forming a CdSe shell.…”
Section: Chemically Triggered Phase Separationmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cd component reacted with the Se, leading to the formation of a Au@CdSe core/shell structure. Pablo et al reported a similar approach to synthesize colloidal Au 2 Cd@CdSe core/shell NPs via AuCd alloy seeds . The internal Cd atoms were partially pulled out to the surface by Se through forming a CdSe shell.…”
Section: Chemically Triggered Phase Separationmentioning
confidence: 99%
“…Pablo et al reported a similar approach to synthesize colloidal Au 2 Cd@CdSe core/shell NPs via AuCd alloy seeds. [ 133 ] The internal Cd atoms were partially pulled out to the surface by Se through forming a CdSe shell. Kuai et al synthesized Au@SnO 2 core/shell NPs via an intermetallics-based dry oxidation method, in which an oxide shell was grown directly from one component of the intermetallic AuSn NPs.…”
Section: Core/shell Structuresmentioning
confidence: 99%
“…Such multifunctional nanomaterials have attracted great interest in last few years due to their distinctive physical as well as chemical properties which lead to admirable performance in electronic, magnetic, photocatalytic, optoelectronic and biological applications over their constituent materials. A wide diversity of metal‐ TMC based hybrid nanostructures such as core‐shell, tetrapod, pentapod, nanoflower, dumbbells etc are reported. Among these hybrid structures, metal/ TMC core‐shell nanocrystals have paid considerable attention for efficient photogenerated carriers for various photoinduced applications .…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, Cd atoms continue to diffuse into the Au lattice until a Au/Cd atomic ratio of 1 is achieved and they eventually recrystallize as CdSe over the metallic tip, contributing to the AuCd encapsulation at late stages of the reaction. (Supporting Figure S3) Au x Cd y binary alloys have been previously observed to be responsible for the growth of Au 2 Cd@CdSe and Au@CdSe core@shell nanoparticles, [50][51] but an anisotropic and epitaxial growth of the cadmium chalcogenide domain as the one reported here has never been achieved up to now. This longitudinal growth mechanism resembles the very well-known SLS mechanism reported by Buhro in 1995.…”
Section: Scheme 1 Reaction and Growth Mechanism Of Au-cdse Hncs In Smentioning
confidence: 65%